Impact of some pollen substitutes in liquid form on the biological activities of honey bee colonies - Abd El-Wahab, T. E.; Ghania, A. M. M. (International Journal of Agricultural Technology, 2016)
This study was conducted to evaluate the effects some commercial liquid formulations of pollen substitute on some biological activities of honey bee colonies. Sixteen colonies of Carniolan hybrid bee (Apis mellifera carinica) colonies of about equal strength and headed by new open mated Carniolan hybrid queens were used for this study. Three groups of honey bee colonies were used to determine the effect three commercial pollen substitutes, Star (Egyptian product), Royal king 4 H (German product) and Royal star (German product) on the biological activities of honey bee colonies. There are significant increases in the mean area of sealed brood in colonies fed with Royal 4H and Royal star more than control colonies during January to March 2014. While, no significant differences between colonies treated with Star formulation and control. During the experimental period Royal 4H formulation recorded a higher significant in the mean number of combs covered with bees in compare with Royal star formulation and sugar syrup (control). Colonies fed with Royal 4H and Royal star recorded significant mean amount of diet consumption by bee colonies during the most experimental periods. The highest significant number of open worker cells contain more one egg, laid by queen, was observed in colonies fed with Royal 4H diet. Feeding with Royal 4H recorded the highest significant number of open worker cells contain more one egg laid by queen especially in December (0.87cell) and February (0.58cell) periods. Also, the results show that the colonies treated by tested diets had a higher number of worker cells which included more one egg than control colonies in the most period of experiment.